1997
DOI: 10.1159/000119346
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Correlates of Personality Traits: A Comparison between Emotionally Stable and Emotionally Labile Healthy Young Men

Abstract: An initial sample of 120 healthy young men was screened by a personality questionnaire and 15 subjects each with highest and lowest scores respectively on emotionality (emotionally labile, EL subjects and emotionally stable, ES subjects) were recruited for a study on the relationship between the degree of emotionality and the basal secretion of stress-sensitive hormones during nighttime. The nocturnal urinary excretion of cortisol, testosterone, adrenaline, noradrenaline and melatonin was measured over a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…However, other studies did not replicate this finding (Adler et al, 1997; Schommer et al, 1999; Ferguson, 2008) and some even reported a negative association between cortisol and neuroticism (Ballenger et al, 1983; LeBlanc and Ducharme, 2005). …”
Section: Introductionmentioning
confidence: 91%
“…However, other studies did not replicate this finding (Adler et al, 1997; Schommer et al, 1999; Ferguson, 2008) and some even reported a negative association between cortisol and neuroticism (Ballenger et al, 1983; LeBlanc and Ducharme, 2005). …”
Section: Introductionmentioning
confidence: 91%
“…One of the most studied factors is the neuroticism-anxiety trait, which is recognized as an important risk factor for the development of depression (Ball and Schottenfeld, 1997;Wang et al, 2002;Sandi and RichterLevin, 2009). The biological significance of neuroticism-anxiety as a predictor of stress-related disorders is supported by a link between this personality trait and basal cortisol levels (Adler et al, 1997;Lindfors and Lundberg, 2002). Using the chronic unpredictable stress (CUS) model of depression (Willner, 1997(Willner, , 2005 in rats, we have identified an association between anxiety trait and both increased vulnerability to stress-induced depression-like symptoms and the response of the amygdala to emotional cues (Sandi et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…This is associated with a higher degree of activation in the amygdala [22,23] and may cause a stronger basal activation of the HPA system in these patients [24] . Both emotional instability [25] and high neuroticism paired with depressive temperament [26] have been shown to be associated with increased stress sensitivity and HPA dysregulation. It is not unlikely that these psychological and neurobiological features are predispositions which make certain individuals vulnerable to develop psychotic symptoms in the course of a depressive episode.…”
Section: Discussionmentioning
confidence: 99%